The cross-cultural process of adapting observational tools for pediatric pain assessment: the case of the Dental Discomfort Questionnaire - Daher, Anelise (BMC Res Notes, 2014)
BACKGROUND: A rigorous cross-cultural adaptation process of an existing instrument could be the best option for measuring health in different cultures, instead of developing a new tool, and prior to psychometric and validation testing. The Dental Discomfort Questionnaire (DDQ), a validated instrument for assessing toothache in young children, has not been cross-culturally adapted so far. This study aimed to explore the detailed phases of the cross-cultural adaptation process of a pain assessment tool, presenting the example of the DDQ Brazilian-Portuguese adapted version. METHODS: The study design was based on the universalist approach, which consists of a sequential analysis to assess the relevant phases of a cross-cultural process before testing the measures of the instrument: conceptual, item, semantic, and operational equivalences. Systematic information was gathered from the literature, expert discussions, translations, and pre-testing through cognitive interviews with Brazilian population. RESULTS: Detailed description of the three major phases for a cross-cultural adaptation process was given. Notes of the changes done in the structure of the presented instrument (DDQ) were specifically pointed out at each phase. Conceptual and item analyses showed that there are similarities in the DDQ construct between the original and Brazilian cultures that require minor modifications. Translations and back-translations allowed the development of the preliminary Brazilian-Portuguese version of the DDQ, which was tested and underwent other minor changes to improve its comprehensibility. CONCLUSIONS: Describing the phases was important to show how changes are made in a cross-cultural adaptation process of an instrument. This also could help researchers in adapting similar pediatric pain assessment tools to different cultures. A Brazilian-Portuguese version of the DDQ was presented. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1756-0500-7-897) contains supplementary material, which is available to authorized users.